Discurso Presidencial e Gênero: análise das mensagens dos presidentes Lula e Dilma ao Congresso Nacional - Valadares, Raquel Gomes (Universidade Federal de São Carlos, 2022)
This work aims investigate how emphasis and positioning regarding the topic of gender modify by comparing two different gender presidents: Luiz Inácio Lula da Silva and Dilma Rousseff. Both are part of the same party – the Workers' Party – which would indicate a continuity of emphasis on agendas and priorities between governments that followed each other and had as a legacy significant advances around policies for minorities. The question that guided the research was: would women place more emphasis on women's (gender) issues when they occupy spaces of power? Thus, analyzing the existence of a rupture in thinking and political positioning between the two presidents was essential in investigating whether the difference in gender roles becomes an element that influences the elaboration of a compatible presidential communicative agenda. To carry out this work, a content analysis (BARDIN, 2009) (KRIPPENDORFF, 1997) of the presidents' messages between the years 2003 and 2016 was carried out, based on lexicometry, using the IRAMUTEQ software. The results showed a greater presence of terms related to gender and policies for women in President Dilma's speeches, pointing to the importance of presence in decision-making and power spaces for modulating the thematic emphases of governments in their communications.
Presidential Speech and Gender: analysis of the messages of presidents Lula and Dilma to the National Congress
Keywords: Lula; Dilma Rousseff; Análise de conteúdo; Iramuteq; Gênero; Discursos presidencial; Gender; Presidential speeches; CIENCIAS HUMANAS::CIENCIA POLITICA::COMPORTAMENTO POLITICO